Activating Lattice Oxygen in Spinel ZnCo2O4 through Filling Oxygen Vacancies with Fluorine for Electrocatalytic Oxygen Evolution - Xiao, Kang; Wang, Yifan; Wu, Peiyuan; Hou, Liping; Liu, Zhao‐Qing (Angewandte Chemie International Edition, 2023)
The development of productive catalysts for the oxygen evolution reaction (OER) remains a major challenge requiring significant progress in both mechanism and material design. Conventionally, the thermodynamic barrier of lattice oxidation mechanism (LOM) is lower than that of absorbate evolution mechanism (AEM) because the former can overcome certain limitations. However, controlling the OER pathway from the AEM to the LOM by exploiting the intrinsic properties of the catalyst remains challenging. Herein, we incorporated F anions into the oxygen vacancies of spinel ZnCo2O4 and established a link between the electronic structure and the OER catalytic mechanism. Theoretical density calculations revealed that F upshifts the O 2p center and activates the redox capability of lattice O, successfully triggering the LOM pathway. Moreover, the high electronegativity of F anions is favourable for balancing the residual protonation, which can stabilize the structure of the catalyst. In this work, we successfully filled the lattice oxygen vacancies of ZnCo2O4 with F atom, achieving the activation of lattice oxygen by regulating metal‐oxygen hybridization, and the dominant oxygen evolution reaction mechanism on ZnCo2O4 can transform from adsorbate evolution mechanism to lattice oxygen oxidation mechanism.